Is repetitive systemic corticosteroid therapy effective for idiopathic sudden sensorineural hearing loss? a retrospective study - Yamamoto, Kengo; Kurioka, Takaomi; Ohki, Motofumi; Sano, Hajime; Yamashita, Taku (Frontiers in Neurology, 2023)
Introduction Some idiopathic sudden sensorineural hearing loss (ISSHL) cases experience repetitive systemic corticosteroid treatment, but studies focusing on repetitive systemic corticosteroid administration have not been reported. Thus, we investigated the clinical characteristics and usefulness of repetitive systemic corticosteroid treatment in ISSHL cases. Methods We reviewed the medical records of 103 patients who received corticosteroids only in our hospital (single-treatment group), and 46 patients who presented at our hospital after receiving corticosteroids in a nearby clinic and were subsequently treated with corticosteroids again in our hospital (repetitive-treatment group). Clinical backgrounds, hearing thresholds, and hearing prognosis were assessed. Results The final hearing outcomes were not different between the two groups. Further, in the repetitive-treatment group, statistical differences were found between the good and poor prognosis groups in the number of days to start corticosteroid administration (p = 0.03), the dose of corticosteroid (p = 0.02), and the duration of corticosteroid administration (p = 0.02) at the previous facility. Multivariate analysis revealed a significant difference in the dose of corticosteroids administered by the previous clinic (p = 0.004). Conclusion The repetitive systemic corticosteroid administration might play a supplementary role in hearing improvement, and initial sufficient corticosteroid administration would lead to good hearing outcomes in an early phase of ISSHL.